Exploration of the influence of different biomimetic designs of 3D printed multi-material artificial spinal disc on the natural mechanics restoration. (15th November 2021) - Yu, Zhiyang; Voumard, Benjamin; Shea, Kristina; Stanković, Tino
Graphical abstract: Highlights: Four 3D printed artificial spinal disc designs show nature-mimicking viscoelastic load response. The four designs also show comparable instant helical axis and center of rotation to a natural disc. Designs that mimic the structure found in a natural disc have big potential for natural mechanics restoration. Design with a chainmail-like structure exhibits nature-mimicking nonlinear rotational load response. Abstract: One of the great challenges of artificial spinal disc (ASD) design lies in the reproduction of the complex mechanics of an intervertebral disc (IVD) that is characterized by a viscoelastic, nonlinear, and anisotropic behavior. Although the development of multi-material additive manufacturing (AM) combined with biomimetic design provide new opportunities for the realization of ASDs with complex behavior, the influence of different biomimetic designs on the kinematics of ASD in conjunction with AM is not yet explored. Therefore, this study proposes and fabricates four types of biomimetic, multi-material ASD designs based on mimicking either the material stiffness gradient or the structure found in a natural IVD. The results show that all the designs exhibit a desired viscoelastic behavior, while the ASD design based on a chainmail-like structure exhibits a nature-mimicking nonlinear rotational load response. In terms of restoring the natural trend of an IVD's anisotropic behavior, the ASD design that mimics the structure found in an IVD outperforms the design that solely mimics an IVD's material stiffness gradient. Additionally, all the designs proposed in this study show comparable instant helical axis (IHA) and instant center of rotation (ICOR) to an IVD's regarding their location and moving direction.